PERAN TASAWUF DALAM PEMBENTUKAN AKHLAKUL KARIMAH PARA PELAJAR - Sabrun Jamil; Rizqi Ajidisira; Karomatul Auliya; Muhammad Amir; Ummi Kalsum; Abdul Fiqar (Yayasan Haiah Nusratul Islam, 2026)
Looking at the facts about the widespread shift in values that is occurring in the world of education, which has an impact on the character of students. The impact of a shift in values is a problem that must be addressed immediately. One suitable way to solve this problem is by applying the values of Sufism. Sufism, which is a path or method of self-purification, is starting to be forgotten and even abandoned by the majority of people, including students. Based on this problem, the author conducte a literature study to find out the application of Sufism in education through character formation. This research also aims to re-ground the science of Sufism in the student environment. From the results of the analysis, the researcher saw that Sufism values such as qana'ah, asceticism, patience and gratitude are values that need to be applied in education. These values will produce students with character and noble morals which is the ideal of education.